Effect of intravenous gentamicin on urinary calcium excretion in newborns - Kurniawan Tan; Adrian Umboh; Ari Runtunuwu (Indonesian Pediatric Society, 2015)
Background Studies in newborns and animals have shown that gentamicin increases urinary calcium excretion. New recommendation for gentamicin in newborns is administered intravenously 36-48 hourly. Subsequent to this new recommendation, there have been no further studies on the effects of extended gentamicin dosage on urinary calcium excretion in newborns.Objective To assess the effect of intravenous gentamicin on urinary calcium excretion in newborns.Methods This pretest â€“ posttest study was done in the Neonatology Division of Prof. DR. R. D. Kandou Hospital, Manado, from August to November 2013. Subjects were full-term newborns who received intravenous gentamicin every 36 hours and whose parents provided informed consent. We excluded newborns with asphyxia and cardiovascular shock, also those who received diuretics or steroids. Urine spot collection was done before, after the first dose, and after the second dose of intravenous gentamicin. Urinary calcium and creatinine levels were measuerd. Urine calcium excretion was defined as the ratio of urinary calcium to creatinine level.Results Of 28 newborns, there were 16 males and 12 females. The median of urine calcium creatinine ratio before intravenous gentamicin was 0.021 (range 0.004 to 0.071) mg/mg. After first dose of gentamicin, the median ratio was 0.043 (range 0.009 to 0.156) mg/mg, and after the second dose of gentamicin, the median ratio was 0.144 (range 0.015 to 1.160) mg/mg.Conclusion There is a significant increase in urinary calcium excretion after the first and second doses of intravenous gentamicin. Furthermore, a cumulative effect of gentamicin on urinary calcium excretion is observed after the second dose.Â